Ordering of Hollow Ag-Au Nanospheres with Butterfly Wings as a Bio-template - Guan, Yu (Sci Rep, 2018)
A biological template strategy is implemented for the fabrication of hollow noble metal composite nanospheres within the ordered array nanostructures by introducing butterfly wings to some convenient technique procedure. Butterfly wings are activated by ethylenediamine to increase the reactive sites on the chitin component, on which Ag nanoparticles are in situ formed and serve as “seeds” to direct further incorporation during the following impregnation procedure. Butterfly wings could function as bio-substrate to provide an ordered array and regulate the synthesis process by providing active reaction sites (e.g. -CONH- and -OH). Thus, hollow Ag-Au nanospheres are loaded on the wings’ surface layer and inside the ordered array nanostructures homogeneously, which would have potential applications in surface enhanced Raman scattering (SERS).